Identification of Tumor Microenvironment-Related Prognostic lncRNAs in Lung Adenocarcinoma - Yuan, Ligong; Li, Feng; Wang, Shuaibo; Yi, Hang; Li, Fang; Mao, Yousheng (Frontiers in Oncology, 2021)
Background: Lung adenocarcinoma (LUAD) is the most common type of lung cancer and is a severe threat to human health. Although many therapies have been applied to LUAD, the long-term survival rate of patients remains unsatisfactory. We aim to find reliable immune microenvironment-related biomarkers to improve LUAD prognosis. Methods: ESTIMATE analysis was performed to divide high and low stromal-score and immune‐score groups in LUAD patients. Correlation analysis was used to evaluate the immune microenvironment-related lncRNAs. Univariate cox regression analysis, Kaplan Meier analysis, and LASSO analysis were used to access the essential lncRNAs' prognostic value. Results: We obtained 1178 immune microenvironment-related lncRNAs after correlation analysis. One hundred eighty out of them are independent prognostic lncRNAs. Sixteen key lncRNAs were selected by LASSO method. All these lncRNAs were related to the OS and pathological stage. Besides, we also found TP53 had the highest frequency mutation in LUAD and the mutation of TP53 in high-risk group which calculated by our survival model have a poor prognosis. lncRNA-mRNA co-expression network further suggested that these lncRNAs play a vital role in the prognosis of LUAD.